Analisis Sosial Media Marketing dalam Membangun Kepercayaan Pelanggan pada Produk Gaskita PT. Perusahaan Gas Negara Tbk, Area Karawang - Sari, Regina Mutiara; Nurlenawati, Netti; Triadinda, Dexi (IPM2KPE, 2024)
This study aims to evaluate the implementation of social media marketing in building customer trust in Gaskita products in the Karawang area. The research method used is a qualitative case study with data validity testing through source and method triangulation. The results of the study indicate that the company has been active in running social media marketing, with the existence of official social media accounts (@gas_negara) and special regional accounts (@gas.karawang). However, although social media marketing has been implemented, the response from customers interviewed indicated that these efforts have not been fully effective in building trust. The conclusion is that although social media marketing has been implemented, the company needs to strengthen this strategy to be more effective in building customer trust. Keywords: Gaskita, Trust, Social Media Marketing